(untitled) (Hekima Review, 2006)
This article seeks to present how the Church handles or should handle the burning issue of teenage mothers in Africa. A teenage mother is a female person aged between and 19 years old, and who has given birth. There are two kinds of teenage mothers, those who are married and those who are not. The latter will be the focus of my article, and I will use the phrase ‘teenage mothers’ or ‘unwed mothers’ indifferently to refer to the same reality.